Post Tensioning Building Analysis Considering Seismic Zone V using Analysis Tools ETABS - Prajapati, Deepak; Bedi, Komal (International Journal of Scientific Research in Civil Engineering, 2019)
In this fast-paced and competitive world, building sector is at the apex of the growth of any country. High-rise buildings are admired by every human being. Traditionally the construction of a building is done by RCC but inpresent world, construction of high rise buildings should be done by Post-Tensioning to resist lateral forces and enhancing structure strength. In RCC, the economic expenditure is very high in commercial and institutional buildings because of more material required in construction and hence, Post Tensioned building proves to be more economic and durable. Post-Tensioned building saves quantity of steel and concrete as compared to RCC and increases clear span in rooms. Through this study, the emphasis is to design a post-tensioned building using ETABS. ETABS stand for Extended Three-Dimensional Analysis of a building systems. The main purpose of this software is to design multistoried building in a systematic process which will be in accordance with Indian Standard design codes. In this comparative study we have consider a unsymmetrical plan of G+9 floors considering Wind load as per I.S. 1983-I:2016 & Black cotton soil. In this study comparative study is done with bare frame building structure considering same loading data to determine maximum storey displacement, axial forces, shear forces, maximum bending, storey drift, stiffness, overturning moment, displacement in x and z direction and cost analysis as per S.O.R.